2011
DOI: 10.1007/s00296-011-2014-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical presentations of hepatitis C virus among patients admitted to the rheumatology ward

Abstract: To study the prevalence of anti-HCV antibodies among patients admitted to the rheumatology department, Cairo University hospitals, in 6-month period as well as to determine whether chronic HCV infection was the primary cause of their admission or just a concomitant association with the rheumatic disease. One hundred and fifty-seven patients were included in this study. They represent all patients admitted to the rheumatology inpatient department of Cairo University hospitals during the study period. Preset que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
1
9
1
2
Order By: Relevance
“…HCV antibodies were present in 20/98 (20.4%) SLE patients (HCV/SLE group), and were absent in 78/98 (79.6%) patients (non-HCV/SLE), of them active viremia (HCV-RNA) was detected in 8/98 (40% of the HCV antibody positive and 8.2% of the studied SLE patients) while the viremia was below the detection level in 12 (60%) of the positive HCV antibody patients. In a recent study in our department, HCV antibodies were found in 6.7% among patients with SLE admitted to the rheumatology ward, Cairo University Hospitals, Egypt [6]. This finding indicated that most patients of SLE and associated anti-HCV antibodies were recruited from the outpatient clinic and that the association between HCV infection and SLE does not imply increased SLE disease [12,29,30].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…HCV antibodies were present in 20/98 (20.4%) SLE patients (HCV/SLE group), and were absent in 78/98 (79.6%) patients (non-HCV/SLE), of them active viremia (HCV-RNA) was detected in 8/98 (40% of the HCV antibody positive and 8.2% of the studied SLE patients) while the viremia was below the detection level in 12 (60%) of the positive HCV antibody patients. In a recent study in our department, HCV antibodies were found in 6.7% among patients with SLE admitted to the rheumatology ward, Cairo University Hospitals, Egypt [6]. This finding indicated that most patients of SLE and associated anti-HCV antibodies were recruited from the outpatient clinic and that the association between HCV infection and SLE does not imply increased SLE disease [12,29,30].…”
Section: Discussionmentioning
confidence: 85%
“…Viruses in general and HCV in particular has been proposed as possible etiologic or triggering factors of many systemic autoimmune rheumatic diseases; most of the previous studies discussed the rheumatic manifestations as a part of the extrahepatic manifestations of chronic HCV infection [6,[24][25][26][27][28]. In this study we studied the prevalence of HCV antibodies among patients with SLE and evaluated the impact of the presence of chronic HCV infection on the SLE disease expression, through comparison of the demographic data, clinical manifestations and disease activity (SLEDAI score) among patients with HCV/SLE and non-HCV/SLE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between HCV and rheumatic diseases is complex and represents both a diagnostic and therapeutic problem to rheumatologists [41]. Management of RA is complicated with the highly significant difference regarding prevalence of HCV in Egyptians.…”
Section: Discussionmentioning
confidence: 99%
“…O Egito tem possivelmente a prevalência mais alta do HCV no mundo, pois o anti-HCV está presente em 11% a 14% da população, ou 8 a 10 milhões de habitantes, dos quais 5 a 7 milhões têm viremia ativa. Nos Estados Unidos, a prevalência do anti-HCV é de aproximadamente 1,6% (El Garf et al, 2012;Armstrong et al, 2006).…”
Section: Epidemiologiaunclassified